Security, data analytics, and energy-aware solutions in the IoT - Hei, Xiali (Advances in web technologies and engineering (AWTE) book series., 2022)
"While the recent rapid proliferation in hardware, software, and communication technologies have facilitated the spread of interconnected sensors, actuators, and heterogeneous devices to collect data for offering a new class of advanced services characterized by being available anywhere, at any time and for anyone, this book addresses these topics across multiple abstraction levels, ranging from architectural models, the provisioning of services, protocols, and interfaces to specific implementation approaches"--